The Quality of Senior High School National School Examination Questions - Mering, Aloysius; Astuti, Indri (Jurnal Ilmu Pendidikan, 2019)
The objective of this study was to obtain information about the quality of high school National Standard School Exam (USBN) questions in Pontianak in 2018/2019 academic year. To achieve this objective, the information excavated includes (a) the process of compiling questions (b) the test of the feasibility of the questions (c) the eligibility requirements of the questions (d) administering the exam (e) the examination system of the examination scripts (f) the reporting system, and (g) the correlation of values report cards and high school USBN grades in Pontianak with UN scores. This study employed a descriptive method. The selection of high school samples used as data sources was done by random sampling and purposive sampling. Data were gathered through documentation, interviews, and questionnaires. The data were then analyzed with descriptive statistics and correlational studies. The results showed that, in the high school USBN questions in Pontianak City, (1) there were still stages in the process of drafting "not done", (2) empirical tests before the compilation of the final questions "had not been done," (3) administering the "already" applied exams as UN procedures, (4) manuscript examination system is implemented manually, (5) reporting of exam results by respective subject teachers, and (6) correlation of report card grades and high school USBN scores in Pontianak with "mostly" low "UN scores "and even in certain" negative "schools. It means that report cards and USBN scores cannot be used to predict UN results.